Electrocardiographic and electrophysiologic differentiation between atriofascicular, long atrioventricular, and short atrioventricular decrementally conducting accessory pathways. Issue 10 (13th December 2017) - Yang, Jian-Du; Zhou, Gong-Bu; Sun, Qi; Guo, Xiao-Gang; Liu, Xu; Luo, Bin; Wei, Hui-Qiang; Liang, Jackson J; Xie, Shuanglun; Ouyang, Fei-Fan; Ma, Jian
Abstract: Aims: We aimed to examine the electrocardiographic and electrophysiologic characteristics of anterograde-conducting decremental accessory pathways (DAP) and to identify surrogate criteria to distinguish short atrioventricular (SAV) DAP from atriofascicular (AF) AP and long atrioventricular (LAV) DAP. Methods and results: We identified all patients with DAPs and analysed electrocardiographic and electrophysiologic characteristics. Distal insertion sites were examined using existing criteria, including V–H interval, ventricular activation at the right ventricular apex, and around tricuspid annulus during antidromic atrioventricular re-entrant tachycardia (A-AVRT) or complete pre-excitation and evaluated the AV node-like properties according to the response to adenosine and radiofrequency ablation. Out of 45 patients with DAPs, 28 (62.2%) had SAV–DAP (13 with definite AF–AP, 2 with definite LAV–DAP, 2 indeterminate). In all, 50% of SAV–DAPs and 53.3% of AF–AP/LAV–DAPs had 'rS' pattern in lead III. Longer QRS duration (159.9 ± 17.4 ms vs. 139.2 ± 14.3 ms, P  < 0.0001) during full pre-excitation or A-AVRT differentiated SAV–DAP from AF–AP. The QRS–V(His) interval was longer for those with SAV–DAP compared vs. AF–AP/LAV–DAP (45.3 ± 2.4 ms vs. 22.9 ± 2.5 ms, P  < 0.0001) and a cut-off value of 33.0 ms differentiated the two (sensitivity 81.3%, specificity 87.5%). Conclusion: The majority of the SAV–DAPs are located at the TA free wall. An 'rS' pattern in lead III is frequently seen in SAV–DAP as well as AF–AP/LAV–DAPs. Measuring the QRS–V(His) interval would be helpful to distinguish SAV–DAP from AF–AP/LAV–DAP.